Delik Adat dalam Sistem Hukum Pidana di Indonesia - Patricia Pasapan; Juanrico Alfaromona Sumarezs Titahelu; Denny Latumaerissa (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The position of Customary offenses (customary crimes) in the Indonesian criminal law system has not yet been explicitly regulated. However, it cannot be denied that customary offenses still exist in Indonesian society, in line with the existence of customary law which includes customary criminal law found in each region across the country.Purposes of the Research: The purpose of this paper/research is to determine the position of customary offenses in the Indonesia criminal law system and to discover the process of handling criminal acts using customary criminal law. Methods of the Research: This research uses normative research methodology or literature study, which is later presented using descriptive research technique that is analysing and explaining the findings of the study.Results of the Research: This research found that, firstly, the criminal law system in Indonesia does not clearly regulate criminal offenses, however, in various regulations, it appears that recognition is given to the customary law which cannot be separated from customary criminal law that regulates the customary offense itself. Secondly, acts which are considered customary offenses will be resolved in a peaceful way by both conflicting parties with the involvement of their traditional leaders. The imposition of customary sanctions is given by agreement of both parties based on conscience and other considerations.